2009
DOI: 10.1021/la901421m
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Efficient Electron Transfer Pathways by Adsorbing Gold Nanoparticles to Self-Assembled Monolayer Modified Electrodes

Abstract: The influence of the length of a self-assembled monolayer (SAM) linker on the electrochemical performance of electrode-linker-gold nanoparticle molecular constructs is investigated. Electrodes were first modified with amino-1-alkanethiols of four different lengths (C=2, 6, 8, and 11). The SAM showed progressively greater blocking ability to ruthenium hexamine as the length of the alkyl chain increased to the point where no significant Faradaic peak was observed for the amino-1-undecanethiol SAM. Upon the attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
175
3
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(200 citation statements)
references
References 55 publications
15
175
3
7
Order By: Relevance
“…17 In terms of electron transfer, Au NPs cannot drive tunnelling across the SiO 2 layer. 18 Rather, both Au NPs and deposited metal can serve as H atom stabilizers, 19 which take H atoms and let them consumed for faradaic reaction more efficiently. Consequently, the amount of electrodeposited Pd increases owing to Au NPs, resulting thin film consisting of Pd-Au alloy NPs on SiO 2 as shown Figure 2 (for detailed characterization, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…17 In terms of electron transfer, Au NPs cannot drive tunnelling across the SiO 2 layer. 18 Rather, both Au NPs and deposited metal can serve as H atom stabilizers, 19 which take H atoms and let them consumed for faradaic reaction more efficiently. Consequently, the amount of electrodeposited Pd increases owing to Au NPs, resulting thin film consisting of Pd-Au alloy NPs on SiO 2 as shown Figure 2 (for detailed characterization, see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AuNPs were synthesized by reduction of tetrachloroauric acid by trisodium citrate following the method described by Gooding et al [13]. The final colloidal gold solution was kept in the dark until use.…”
Section: Synthesis and Characterization Of Gold Nanoparticles (Aunps)mentioning
confidence: 99%
“…Preliminary experiments showed that this treatment performed on NEEs does not change their electrochemical performances. Cysteamine is to be preferred to dithiols because it cannot form multilayers or disulfide bridges [13]. Previous studies showed that SH terminal groups bind preferentially to gold surfaces leaving the amino groups available for the subsequent NPs immobilization [13].…”
Section: Fabrication Of Nees and Modification With Aunpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, assembling the surface functional NPs onto electrode was commonly used to form modified electrode [17,18]. Generally, in this method, ligands with strong affinity to Au (such as thiol) was adopted to react with weak ligands (such as citrate [19] and phenylphenol [20]) protected Au NPs, forming functional Au NPs, and then the functional NPs were adsorbed onto the electrode surface to form NPs modified electrode. However, the electrochemical sensitivity of as-prepared modified electrode is greatly reduced due to the surface of NPs are tightly wrapped by functionalized organic molecules.…”
Section: Introductionsmentioning
confidence: 99%